Intimate partner violence and women's reproductive health. Issue 5 (May 2017) - Fanslow, Janet
Abstract: Intimate partner violence (IPV) is common among women. An estimated 30% of all women globally report experiencing physical or sexual violence by a husband, intimate partner or ex-partner. It is important for those working in reproductive health settings to be aware that sexual assault can occur in the context of relationships. IPV can also include reproductive and sexual coercion. Reproductive coercion includes behaviours that interfere with contraception use and/or pregnancy, while sexual coercion includes behaviours related to pressuring or coercing a person to have sex without using physical force. Past or current IPV in a woman's life can have profound implications for all aspects of her reproductive health, and healthcare providers need to have the skills to identify IPV, and provide appropriate support and referrals as required.